Simultaneous application of transcranial magnetic stimulation and low-frequency electrostatic field as treatment of carbohydrate and lipid disorders in patients with metabolic syndrome - Andrey A. Benkov; Sergey N. Nagornev; Valery K. Frolkov; Valentine F. Reps; Dmitriy A. Edelev; Anatoly D. Fesyun; Maxim Yu. Yakovlev; Natalia Fedorovna Tumanova; Natalia P. Sanina; Maria Chiara Maccarone; Stefano Masiero (PAGEPress Publications, 2022)
The metabolic syndrome, which covers a wide variety of pathological concerns, is rapidly becoming a global pandemic. This syndrome is difficult to treat pharmacologically. Physiotherapy techniques, which have both local and systemic effects, can be employed as a suitable substitute. The purpose of this study was to investigate the therapeutic effects of a program of simultaneous physiotherapy that included migrant transcranial magnetic stimulation (TMS) and the exposure to an alternating low-frequency electrostatic field (LFEF) in the treatment of metabolic syndrome patients. Ninety patients were randomly assigned to three study groups. While continuing the usual drug therapy the first group (30 patients) received LFEF intervention, the second group (30 patients) received TMS, and the third group (30 patients) underwent the simultaneous use of these non-invasive techniques (LFEF + TMS). All treatments involved 10 sessions with daily frequency. In all the patients before and after treatment body weight, blood pressure parameters, levels of insulin, cortisol, glucose, total cholesterol, high density lipoproteins, malondialdehyde, and Schiff bases, the activity of the antioxidant enzymes catalase and of the superoxide dismutase were studied. The changes in the outcomes assessed revealed a different reaction to therapy with LFEF or TMS, as well as a greater benefit when both treatments were used at the same time. A simultaneous LFEF and TMS intervention seems a promising resource for the treatment of the metabolic syndrome, particularly of the lipid and carbohydrate metabolism disorders. However, further studies are needed to confirm these findings and investigate the underlying mechanisms.